EFFECTS OF CYCLOSPORINE-A IMMUNOSUPPRESSION ON PANCREATICODUODENAL TRANSPLANTATION IN ALLOXAN-DIABETIC RATS - Spadella, César Tadeu [UNESP]; Breim, L. C.; Mercadante, MCS; Machado, JLM; Demacedo, A. R. (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
1. Forty-five outbred Wistar rats were randomly assigned to three experimental groups: GI, 10 non-diabetic control rats; GII, 10 alloxan-diabetic control rats; GIII, 25 alloxan-diabetic tats which received pancreaticoduodenal transplantation (PDT) from normal Wistar donor rats and were immunosuppressed with cyclosporin A (Cy-A), 10 mg kg body weight-1 day-1, administered intraperitoneally for 30 days.2. In parallel, 15 alloxan-diabetic inbred Wistar rats received isogeneic PDT from normal Wistar donor rats.3. Cy-A prevented graft rejection in the 15 surviving animals in group III. These observations were confirmed by clinical and biochemical parameters (body weight, urine output, water and food intake, blood and urinary glucose and plasma insulin) and by histology and immunohistochemistry of the pancreas.4. However, Cy-A was associated with 60% of the infectious complications in transplanted rats leading to 40% mortality. Pulmonary infections were the main cause of death. There were no side effects of immunosuppression on the pancreas. Infections were not significant in inbred rats submitted to PDT.
Keywords: PANCREAS TRANSPLANTATION; EXPERIMENTAL DIABETES; ALLOXAN-INDUCED DIABETES; CYCLOSPORINE